Implementation of Quaternary Prevention in the Korean Healthcare System: Lessons From the 2015 Middle East Respiratory Syndrome Coronavirus Outbreak in the Republic of Korea - Bae, Jong-Myon (J Prev Med Public Health, 2015)
Quaternary prevention should be implemented to minimize harm to patients because the ultimate goal of medicine is to prevent disease and promote health. Primary care physicians have a major responsibility in quaternary prevention, and the establishment of clinical epidemiology as a distinct field of study would create a role charged with minimizing patient harm arising from over-medicalization.